Reputation as a Disciplinarian of International Organizations. Issue 2 (9th April 2019) - Daugirdas, Kristina
Abstract: As a disciplinarian of international organizations, reputation has serious shortcomings. Even though international organizations have strong incentives to maintain a good reputation, reputational concerns will sometimes fail to spur preventive or corrective action. Organizations have multiple audiences, so efforts to preserve a "good" reputation may pull organizations in many different directions, and steps taken to preserve a good reputation will not always be salutary. Recent incidents of sexual violence by UN peacekeepers in the Central African Republic illustrate these points.